CC and CXC chemokines are pivotal mediators of cerebral injury in ischaemic stroke - Mirabelli-Badenier, Marisol; Braunersreuther, Vincent; Viviani, Giorgio Luciano; Dallegri, Franco; Quercioli, Alessandra; Veneselli, Edvige; Mach, François; Montecucco, Fabrizio (Thrombosis and Haemostasis, 2011)
The definition of ischaemic stroke has been recently updated as an acute episode of neurological dysfunction caused by focal brain, spinal cord, or retinal ischaemia in the presence of a cerebral infarction. This “tissular” definition has highlighted the importance of pathophysiological processes underlying cerebral damage. In particular, post-ischaemic inflammation in the brain and in the blood stream could influence crucial steps of the tissue injury/repair cascade. CC and CXC chemokines orchestrate the inflammatory response in atherosclerotic plaque vulnerability and cerebral infarction. These molecules exert their activities through the binding to selective transmembrane receptors. CC and CXC chemokines modulate crucial processes (such as inflammatory cell recruitment and activation, neuronal survival, neoangio-genesis). On the other hand, CXC chemokines could also modulate stem cell homing, thus favouring tissue repair. Given this evidence, both CC and CXC chemokines could represent promising therapeutic targets in primary and secondary prevention of ischaemic stroke. Only preliminary studies have been performed investigating treatments with selective chemokine agonists/antagonists. In this review, we will update evidence on the role and the potential therapeutic strategies targeting CC and CXC chemokines in the pathophysiology of ischaemic stroke.
Keywords: Stroke/prevention; chemokines; inflammatory mediators